Efektivitas Media Papan Pintar Terhadap Kemandirian Belajar Kelas IV SD Negeri Mangkubumen Wetan Surakarta - Rizky; Ema Butsi Prihastari; Mukhlis Mustofa (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of using smart board media on the learning independence of fourth-grade students at SDN Mangkubumen Wetan, Surakarta. The background of the study is based on the low level of student learning independence, as indicated by a lack of self-confidence, high dependence on teachers, and minimal active participation in the learning process. The study employed a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 28 students selected using a saturated sampling technique. Data were collected through a learning independence questionnaire, observation, and documentation. The research instruments were tested for validity and reliability. Data analysis included normality testing, paired sample t-test, and N-Gain test. The results showed that the average pretest score was 70.62 (71%), and the posttest score was 86.38 (86%). The paired sample t-test showed a significance value of 0.000 (< 0.05) and a t-value of 11.941 > t-table value of 2.052, indicating a significant difference between the pretest and posttest scores. Furthermore, the N-Gain test results showed an increase of 62.49, which is categorized as moderately effective in improving the learning independence of fourth-grade students in mathematics at SDN Mangkubumen Wetan Surakarta.